EFL STUDENTS’ PREFERENCES FOR CLASSROOM FEEDBACKS - Asfar Arif Nurharjanto (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
Language learners’ environment holds vital contribution to learners’ language development. It provides them with the target language, in this case, English as a Foreign Language, which is usually taken in the form of input and feedback. Learners may choose the feedback variously depending on their proficiency and background. However, prior studies in this area show inconsistent results regarding the effect of learners’ background and proficiency on their preference for feedback.  Hence, this study aimed to explore EFL University students’ preferences for classroom feedback. The data were gained through interviews involving 20 students of the Graduate Program of English Education whose English competencies are mostly upper intermediate to advanced level. This study found that the learners could accommodate all types of given feedbacks and they do not significantly tend to choose particular types of feedback. This implies that learners’ language proficiency and surrounding environment could determine their choice of feedback. As a result, teachers or other language trainers should take their learners’ current language development into account in order to give those appropriate types of feedback.